Perempuan dan Peran Regenerasi dalam Lingkaran Ekstremisme Kekerasan: Narasi dari Indonesia Timur - Muhammad Najib Azca; Rani Dwi Putri (Jurnal Sosiologi Agama, 2021)
This article argues the important roles played by women either in the act of violent extremism or in its countering by focusing particularly on the issue of regeneration. Through their traditional roles as a mother and wife, women can affect, manage, or even to a certain extent shape the choice of a family either to keep or to discharge violent extremism ideology in the family circle. The study was carried out in Poso, a small town in Central Sulawesi, Eastern Indonesia, which has experienced communal conflict between Muslim and Christian communities that eventually been transformed into violent extremism acts by jihadi-terrorist actors. Through conducting fieldwork in 2019 and continuing with an ‘in-distance study’ using communication technology in 2020, the study employed a qualitative method by interviewing 30 women in Poso. Following Vigh (2006) and Sjoberg & Gentry (2011), it contends that woman as agency carries out social navigation in dealing with uncertainties and socio-political crises as the consequence of protracted violent conflict in the area. This study concludes that despite being situated in the circles of jihadism which are more dominated by masculine character, women’s agency emerges in two forms: first, in nurturing and maintaining the ideology of violent extremism through inheriting revenge narratives, choosing a school, and involving children in extremism activities. Second, some women opt to leave violent circles off in their families by disclosing the spaces for dialogue and opening reflective personal communication with their children to provide broader viewpoints and non-violence values. The article closes with a reflection on the dynamic relations between mother and children as a pivotal factor in the regeneration process of violent extremist groups based on biographic narratives of mother and children in jihadi-terrorist family.